MICROBIAL CONTAMINATION IN MIXED SYRUP CONTAINING ERDOSTEIN AND CETIRIZIN STORED AT DIFFERENT STORAGE TEMPERATURE - Cahyanti, Naomi Dwi; Purwaningsih, Hesti; Angelia, Inez; Deki, Yohanes Damasus Natanael; Ramadhan, Gilang (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
Pharmaceutical services include drug dispensing activities, including drug compounding. Drug compounding is the process of mixing or changing ingredients to produce drugs that suit patient needs. Unmonitored storage conditions for compounded drugs in the community can affect the evaluation of the physical, chemical, and microbial contamination stability. The aim of this study was to determine the effect of storage temperature on the results of the evaluation of microbial contamination in compounding syrup pharmaceuticals, so it can provide education to the public about the storage patterns that have been carried out so far. Evaluation of microbial contamination in this study included contamination of the Total Yeast and  Mold Count (TYMC) and Total Plate Count (TPC). The objective of this study was a mixture of Erdostein syrup and cetirizine tablets. The research materials used for the microbial contamination test were mineral water, sterile water, Plate Count Agar (PCA) media, and Potato Dextrose Agar (PDA). The results of the study in the form of TYMC and TPC on day 0 were 0 cfu/mL. After 7 days of storage, microorganisms, namely TYMC, grew at room temperature (<30°C) 4.98x102 cfu/mL and cold temperature (2-8°C) 2.2x102 cfu/mL. The TPC results at room temperature storage (<30°C) were 8.33x102 cfu/mL and at cold temperatures (2-8°C) were 3.67x102 cfu/mL ...